How the body works skin, bones and muscles (Chatsworth, CA : AIMS Multimedia, 1997)
This cd-rom program contains complete linear video, interactive quiz with video reinforcement, bulletin board, glossary, test with record keeping and teacher management system.
Cd-rom is available at Makmal Digital, PPKL
System requirements : Macintosh ; drag folder to your hard drive then double click on the program icon.
System requirements :Windows ; run' install.exe' from cd-rom then double click on the program icon..
Keywords: Musculoskeletal system; Skin; Muscles